Prolonged diet-induced obesity modifies DNA methylation and gene expression in the hippocampus. (29th May 2022) - Vander Velden, Jacob W.; Osborne, Danielle M.
Graphical abstract: Highlights: Obesogenic diet exposure results in differentially methylated regions of DNA in the hippocampus of male mice. Effects of the diet on hippocampal methylation were greater the longer the mice spent on the diet. Aging alone in control mice changed hippocampal methylation, albeit not as greatly as in obese mice. Methylation results corresponded to significant changes in mRNA expression of genes related to neurodegeneration including HDAC5 and BIN1. Abstract: Obesity and age independently have negative effects on the brain, increasing the risk of neurodegenerative events. How these events synergize to increase disease susceptibility remains poorly understood. To better understand the epigenetic implications of poor diet with increased age, we sought to determine CpG methylation changes in the dorsal hippocampus attributable to age and/or diet-induced obesity. Male C57BL/6J mice were fed either normal chow or an obesogenic diet until six or 14 months of age. Hippocampus was analyzed by Reduced Representation Bisulfite Sequencing. In total, 107 differentially methylated regions (DMRs) were identified across all four conditions; older obese mice accounted for 63% of those DMRs. Gene ontology analysis showed two affected pathways, nervous system development and regulation of multicellular organismal process, in older obese mice only. From the RRBS results, five genes were selected for qPCR quantification: Bridging Integrator 1 (BIN1), Histone Deacetylase 5 (HDAC5), Folliculin Interacting Protein 2 (FNIP2), Proline, Glutamate and Leucine Rich Protein 1 (PELP1), and Protein Tyrosine Phosphatase Non-Receptor Type 1 (PTPN1). Generally, DMR changes aligned with mRNA expression changes in BIN1, HDAC5, FNIP2, PELP1, and PTPN1. Notably BIN1 decreased and HDAC5 increased due to obesity and age. In summary, obesity interacts with aging to significantly affect the hippocampal methylome, changing the expression of genes implicated in neurodegeneration and metabolism.